Malcolm Forsyth’s Double Concerto: Forging a New Simplicity - Rival, Robert (Intersections, 2019)
In 2004, Canadian composer Malcolm Forsyth (1936–2011) stated publicly that the simplest compositions, if genuine, often achieved the greatest profundity. He described the Adagio from his Double Concerto for Viola and Cello (2004) as “the greatest departure, for me, to this realm of a very, very simple and harmonious music.” This article explores Forsyth’s conception of simplicity by placing a close harmonic, motivic, and structural analysis in several contexts: the work’s history of revisions, what Mozart, Schubert, and Brahms reveal about musical simplicity, the debate on profundity in music, the discourse on “late style,” and personal anecdotes.